The distinct effects of information technologies and communication technologies on the age-skill composition of labour demand - Sotiris Blanas (National Bank of Belgium, 2019)
This paper is the first to study the distinct effects of Information Technologies (IT) and Communication Technologies (CT) on the skill, age, and age-skill composition of labour demand. The analysis is conducted on a sample comprising 10 developed countries, 30 industries covering the largest part of the economy, and the period 1982-2005. I find that IT intensity increases the relative demands for the high-skilled, low-skilled and oldest workers, while it decreases the relative demands for the medium-skilled and younger workers. Also, IT intensity increases the relative demands for the high-skilled and low-skilled of all age profiles, while it decreases the relative demands for the medium-skilled of all age profiles. CT intensity exerts opposite effects. Consistent with knowledge-based hierarchy theories highlighting the organisational aspect of the adoption of IT and CT by firms, the empowerment of agents at lower and higher levels of the hierarchy induced by IT and CT, respectively, rationalise these findings. I also find that the aforementioned effects operate mostly as of 1990, when the advancement rates of IT and CT were even higher than in the 1980s. Although a clear pattern of disproportionate effects across sectors is not identified, such a pattern across countries does exist: the inequalities generated by the two types of technologies are mitigated by higher union density.
Keywords: O33; J21; J23; J24; J31; 330; Information Technologies; Communication Technologies; relative labour demand; age-skill profile